2020
DOI: 10.1136/bmjopen-2020-039288
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age at delivery and risk of allergy and asthma in the offspring: a systematic review and meta-analysis protocol

Abstract: IntroductionWhile several perinatal factors have been linked to the risk of developing asthma and allergy in childhood, the role of maternal age at delivery remains uncertain. Some studies suggest that young maternal age at delivery may increase the risk, while other studies suggested a reduced risk. To provide a clearer appreciation of the underlying evidence, we plan to undertake a systematic review to synthesise previous studies that have investigated the association between maternal age at delivery and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this systematic review, some studies found that advanced maternal age is associated with an increased risk of asthma, while, other studies found this association in children born to younger mothers, or reported no association (54).…”
Section: Maternal Agementioning
confidence: 88%
See 1 more Smart Citation
“…In this systematic review, some studies found that advanced maternal age is associated with an increased risk of asthma, while, other studies found this association in children born to younger mothers, or reported no association (54).…”
Section: Maternal Agementioning
confidence: 88%
“…Maternal age at delivery has been extensively investigated as a possible risk factor for childhood asthma. However, according to a recent systematic review, there are some inconsistencies in the associations of maternal age at delivery and childhood asthma (54).…”
Section: Maternal Agementioning
confidence: 99%